Screening of EWI-2-Derived Peptides for Targeting Tetraspanin CD81 and Their Effect on Cancer Cell Migration - Thanawat Suwatthanarak; Kei Usuba; Kotomi Kuroha; Masayoshi Tanaka; Mina Okochi (Biomolecules, 2023)
CD81, a transmembrane protein belonging to the tetraspanin family, has recently been suggested as a therapeutic target for cancers. Here, we screened peptides that bind to the tetraspanin CD81 protein, and evaluated their inhibitory activity in cancer cell migration. To screen for CD81-binding peptides (CD81-BP), a peptide array membrane was prepared from the amino acid sequence of the EWI-2 protein, a major partner of CD81, before binding to fluorescently labeled CD81. As a result, four candidate CD81-BPs were identified and characterized. In particular, the CFMKRLRK peptide (called P152 in this study) was found to be the best candidate that preferentially binds to the extracellular loop of CD81, with an estimated dissociation constant of 0.91 µM. Since CD81 was reported to promote cancer cell migration, an initial step in metastasis, the Boyden chamber assay, was next performed to assess the effect of CD81-BP candidates on the migration of MDA-MB-231 human breast cancer cells. Interestingly, our result indicated that P152 could suppress MDA-MB-231 cell migration at the level comparable to that of an anti-human CD81 antibody (5A6). Thus, we propose these CD81-BPs with the anti-migration property against cancer cells for the development of novel therapeutic strategies.